DETERMINANT OF CAPITAL STRUCTURE OF PROPERTY & REAL ESTATE COMPANIES IN INDONESIA STOCK EXCHANGE - Surya Alam, Muhammad; Augustina Kurniasih (Dinasti International Journal of Economics, Finance & Accounting, 2020)
This studyf aims to analyzef the factorsf that influencef the capital structuref of property & realf estate companies containedf on the IDXf in 2017 2018. The dataf used is secondaryf data and the methodf used is panelf data regression analysisf with the helpf of the Eviews 10 applicationf to obtainf aff comprehensive picturef of the relationshipf between variables with other variables. The samplef in thisf study consisted of 47ff property & real estate companiesf listed on the IDX inf 2017 2018. the resultsf off this study aref profitability and assetf structure has a significantf influence on capitalf structure. liquidity, growthf and sizef have no influencef on capitalf structure. The resultsf of the simultaneousf regression analysisf state that the profitabilityf off the asset liquidityf growth structuref and sizef affect the capitalf structure